CAREER MANAGEMENT DAN SUBJECTIVE CAREER SUCCESS: DAPATKAH MENINGKATKAN KEPUASAN KERJA WANITA KARIR? - Sylvia Diana Purba (MIX: JURNAL ILMIAH MANAJEMEN, 2017)
Abstract. This study aims to examine the effects of work-life balance and subjectivecareer success in career management influence on job satisfaction in female workers.Data were collected with convinience sampling technique in 91 women employees insome of the Bank in Jakarta. Using the data have proven the validity and realibilty,Hypotheses test by using SPSS V.22 software and macros inderect Hayes 2013. Thetest results prove work-life balance and subjective career success significant asintervening variable on effect of career management toward job satisfaction. While adirect influence of career management on job satisfaction is not significant, so thatmediation be a perfect mediation.Keywords: career management, work-life balance, subjective career success, jobsatisfaction